2014
DOI: 10.15312/eurasianjvetsci.201436515
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological studies of fascioliasis (Fasciola gigantica) in black Bengal goats

Abstract: keçilerinde fascioliasisin (Fasciola gigantica) epidemiyolojik çalışması. Amaç: Siyah Bengal keçilerinde farklı yaş, cinsiyet ve mevsimde facioliasisin epidemiyolojisini araştırmaktır. Gereç ve Yöntem: Siyah Bengal keçilerindeki fascioliasisinin epidemiyolojik araştırması Upazilla'nın beş farklı bölgesinin Sylhet bölgesinde farklı iklim koşulları altında gerçekleştirildi. Keçiler genç ve yaşlı olmak üzere iki gruba ayrıldı. Temmuz 2012-Haziran 2013 döneminde çiftliklerdeki keçilerden rektal sıvap örnekleri ve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…The prevalence of fascioliasis in slaughtered animals has been reported to be 15–66% in cattle [14, 28], 3.8–22% in goats [17, 29–31], 81% in sheep [32] and 23–47% in buffaloes [22, 33], respectively. The actual burden of fascioliasis - including subclinical disease - is likely much higher than that reported above [34].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of fascioliasis in slaughtered animals has been reported to be 15–66% in cattle [14, 28], 3.8–22% in goats [17, 29–31], 81% in sheep [32] and 23–47% in buffaloes [22, 33], respectively. The actual burden of fascioliasis - including subclinical disease - is likely much higher than that reported above [34].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of fascioliasis in Bangladesh in live animals has been reported to vary from 21 to 53% in cattle [ 6 – 16 ], 10 to 32% in goats [ 15 – 19 ], 8.4 to 31% in sheep [ 16 , 18 , 20 ] and 19 to 51% in buffaloes [ 15 , 16 , 21 – 27 ]. The prevalence of fascioliasis in slaughtered animals has been reported to be 15–66% in cattle [ 14 , 28 ], 3.8–22% in goats [ 17 , 29 – 31 ], 81% in sheep [ 32 ] and 23–47% in buffaloes [ 22 , 33 ], respectively. The actual burden of fascioliasis - including subclinical disease - is likely much higher than that reported above [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various constrains in the development of cattle, both infectious and noninfectious diseases are the most important limiting factors that cause significant mortality of adult cattle and neonatal calves each year (Debnath et al 1990, Debnath et al 1995. It was reported that variation in different cattle breed, their sex and environmental factors greatly influence the disease prevalence in livestock animals including cattle (Alim et al 2011, Sarker et al 2011, and Islam et al 2014). The present study was undertaken to investigate the prevalence of cattle diseases considering breed, sex and seasons at five different locations of Chittagong division in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Fasciola gigantica is one of the most endemic and parasitic diseases of ruminants in Bangladesh (Amin and Samad, 1988; Islam and Samad, 1989; Rahman et al ., 2017). The prevalence of F. gigantica in live animals has been reported to vary from 21 to 53% in cattle, 10 to 32% in goats, 8.4 to 31% in sheep and 19 to 51% in buffaloes (Islam et al ., 2014; Rahman et al ., 2017) and its prevalence in slaughtered animals also vary from 15 to 66% in cattle, from 3.8 to 22% in goats, 81% in sheep and from 23 to 47% in buffaloes, respectively (Talukder et al ., 2010; Islam et al ., 2014). However, the actual burden of F. gigantica in domestic ruminants might be much higher than the mentioned values since fascioliasis is mainly the subclinical disease (Khatun et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%